The Role of Technostress on Educators' Work Performance at Universities in the Special Capital Region of Jakarta - Dina Syakina; Aulia Rahma; Mohammad Rizal (Universitas Katolik Soegijapranata, 2023)
The COVID-19 pandemic forced the education system to adapt a new teaching system from offline to online. However, the ability of lecturers is often unable to keep up with rapid technological developments and the lack of resources provided by institutions, causes lecturers to feel stressed during the teaching and learning process. This study aims to determine the effect of technostress on lecturer performance using the Person-Organization Fit theory approach. The results showed that at the organizational level, the discrepancy between abilities and demands (AD-O) (B= -.39; p.01) had a significant negative and positive effect on lecturer needs with supplies (NS-O) (B=. 24;p.05) with performance. At the individual level, the mismatch between needs and supply (NS-T) (B=-.51; p.01), the absence of social support from colleagues (PPF) (B=-.32; p.01) had an effect significant negative. The findings of this study indicate that both the organizational level and peer support (AD-O and PPF) as well as the individual level (NS-T) play an important role in predicting a decrease in lecturer performance, while the mismatch between ability demands at the individual level has no effect on performance. The implications of this research will be discussed further in the discussion.